2022
DOI: 10.1002/cam4.5237
|View full text |Cite
|
Sign up to set email alerts
|

Watchful waiting is an acceptable treatment option for asymptomatic primary ocular adnexal mucosa‐associated lymphoid tissue lymphoma: A retrospective study

Abstract: Background Primary ocular adnexal mucosa‐associated lymphoid tissue (MALT) lymphoma (POAML) is the most common subtype of indolent ocular adnexal lymphomas. Although radiotherapy (RT) is the standard of care for localized POAML, it can occasionally lead to permanent side effects. Other treatment strategies, such as rituximab (R) monotherapy and immunochemotherapy, have been used for POAML treatment, but their long‐term benefits and relative merits remain unclear. While watchful waiting (WW) is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Another study compared upfront radiotherapy with intravenous Rituximab monotherapy for both conjunctival and orbital type MALT lymphomas. After a median follow up of 48.8 months, the 5-year PFS rate in the Rituximab group (n = 19) was 41.4% compared to 67.4% in the radiotherapy group (n = 24) [36]. A large multicenter, retrospective cohort study showed a significantly better 10-year disease specific survival for stage I ocular MALT lymphoma patients when treated with radiotherapy rather than systemic treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Another study compared upfront radiotherapy with intravenous Rituximab monotherapy for both conjunctival and orbital type MALT lymphomas. After a median follow up of 48.8 months, the 5-year PFS rate in the Rituximab group (n = 19) was 41.4% compared to 67.4% in the radiotherapy group (n = 24) [36]. A large multicenter, retrospective cohort study showed a significantly better 10-year disease specific survival for stage I ocular MALT lymphoma patients when treated with radiotherapy rather than systemic treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, fear of orbital toxic effects has prompted some physicians to observe patients with newly diagnosed indolent BCL in lieu of immediate RT . In a study of 75 patients with orbital MALT lymphoma, 29 underwent watchful waiting as opposed to therapy . No meaningful differences were noted between groups in the time to start a new therapy.…”
Section: Discussionmentioning
confidence: 99%